2021
DOI: 10.1002/ldr.4116
|View full text |Cite
|
Sign up to set email alerts
|

Ecological network analysis to assess the restoration success of disturbed mine soil in Zoucheng, China

Abstract: Understanding the interactions among soil microbial species and how they respond to land reclamation is essential to evaluate the success of ecological restoration actions in disturbed mine soil. In this study, we strived to reveal the interactions among soil bacterial communities along the reclamation timeline of a coal mine in Zoucheng, China. To do so, we investigated changes in the composition of soil bacterial over time and constructed molecular ecological networks (i.e., microbial network) following mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 96 publications
(144 reference statements)
1
12
0
Order By: Relevance
“…For the subsoil, Rokubacteria was positively correlated with pH, while Chloroflexi and Acidobacteria were positively correlated with AN, SOM, AP, TC, AK, and TN. These results suggested soil pH was a key driving factor for bacterial community structure (Ma et al, 2020;Ma et al, 2021), and further confirmed that soil nutrients can significantly influence soil bacterial communities in different reclamation areas (Wan and He, 2020).…”
Section: Impacts Of Soil Physicochemical Properties On Soil Microbial...supporting
confidence: 55%
See 3 more Smart Citations
“…For the subsoil, Rokubacteria was positively correlated with pH, while Chloroflexi and Acidobacteria were positively correlated with AN, SOM, AP, TC, AK, and TN. These results suggested soil pH was a key driving factor for bacterial community structure (Ma et al, 2020;Ma et al, 2021), and further confirmed that soil nutrients can significantly influence soil bacterial communities in different reclamation areas (Wan and He, 2020).…”
Section: Impacts Of Soil Physicochemical Properties On Soil Microbial...supporting
confidence: 55%
“…For instance, coal consumption in China accounted for 56.8% of the total energy consumption in 2020 (Hu et al, 2022), and coal consumption will continue to grow by 3.4% in the next 20 years (Yu et al, 2022). The extensive exploitation of coal resources has caused serious environmental and social problems including land subsidence, land damage, and poor harvest (Wang et al, 2020;Ma et al, 2021). In high groundwater level areas, coal mining always resulted in land subsidence and changed terrestrial to aquatic ecosystems (Ma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This area has a good ecological foundation and is located in the less affected natural mountainous area to the north of the mining area, so the ecological spontaneous succession is faster after the mine stops mining. Agricultural means reduce the secondary damage to the site caused by guest soil restoration and chemical improvement [ 50 ] and at the same time promote local farmers to increase income while ecological restoration, taking into account the production value of the site, which provides a strong long-term drive for ecological restoration in the region and promotes the ecological transformation of the regional economic and social production methods and sustainable development [ 51 ].…”
Section: Discussionmentioning
confidence: 99%